"There is a chain of Chinese whispers …": empirical data support the call to formally teach handover to prequalification doctors. Issue 4 (3rd August 2009) - Cleland, J A; Ross, S; Miller, S C; Patey, R
Abstract : Background: Changing patterns of work in the hospital setting mean different teams look after the same group of patients over the course of any given day. Shift handovers, or hand/sign-off, can give rise to miscommunication of critical information, a patient safety issue. How can we best prepare new doctors for handover? Methods: This was a qualitative, focus-group study, exploring the views of doctors (Foundation Year, Senior House Officers, Registrars and Consultants) and night nurse practitioners, in Aberdeen, UK. Results: Five focus groups were carried out with 21 participants. Using framework analysis, five main themes relevant to the task of effectively handing over, and how to best teach handover, emerged. These were: definition of handover; experience of handover as a junior doctor; perceptions of junior doctors' handover skills and attitudes; systems factors, and their interaction with individual factors; and the "what" and the "how" of teaching handover. Conclusions: New doctors feel unprepared for handover and are seen as poor at handing over. Certain skills are required for effective handover, but professional attitudes are also critical. The skills identified reflect those suggested in policy documents based on expert panel views. Poor systems are a barrier to effective learning and practice. Our empirical approach adds to existing knowledge by highlighting that handover is not solely a skills-based task; there are complex interactions between individual and systems factors; and junior doctors should be prepared for handover prequalification. These data can be used to plan optimal handover teaching for medical students.